RETRACTED: FEM analysis of the impact of surface undulations on the natural convective flow of viscous fluid in a permeable trapezoidal enclosure - Bilal, Sardar; Khan, Noor Zeb; Eldin, Sayed M. (Frontiers in Physics, 2023)
Examination about transport mechanism in permeable trapezoidal enclosure with undulation effect is commenced. Formulation describing naturally convective flow in permeable domain is conceded by employing Boussinesq and Darcy approximations. Uniform temperature is provided at circular cylinder and base wall of enclosure whereas, non-parallel side extremities are kept cold. No heat flux condition is applied at wavy surface (upper) to maintain potential difference in temperature for generation of convection. Finite element scheme is opted to resolve governing system for accounted physical problem. Grid sensitivity test is also executed to assure credibility of code and results. Wide range of physical parameters are selected to comprehend their impact on stream lines and isotherm patterns. Results are revealed in comparative manner for zero undulation (upper solid straight wall) and with undulations (wavy wall). Heat flux and kinetic energy are also enumerated as key quantities against concerning parameters. It is depicted that average Nusselt number and kinetic energy is more in the absence of undulations in comparison to situation when it is present. Additionally, it is manifested that placement of heated cylinder assist in transfer of heat in domain and also in production of thermal convective potential.